Stock assessment of the lizardfish Saurida tumbil (Bloch, 1795) in Jizan fisheries, Saudi Arabia - Mohamed Hosny Gabr (Egyptian Journal of Aquatic Research, 2017)
To evaluate the current stock status of the lizardfish Saurida tumbil in Jizan fisheries, growth parameters, mortality coefficients and size at first capture were determined. Otoliths collected from 623 specimens were used for age determination and back calculations of lengths at ages. The growth parameters of von Bertalanffy were estimated and found to be L∞ = 52.98 cm, K = 0.27 yr−1, and to = -0.84 yr. The mortality coefficients were estimated to be 1.365, 0.403 and 0.962 yr−1 for the total 'Z', natural 'M', and fishing 'F' mortality coefficient, respectively. The current exploitation rate 'Ecur' was 0.705 yr−1. The length at first capture 'Lc' was determined to be 25.1 cm. The relative yield and biomass per recruit were estimated, and the results showed that the exploitation rate is currently higher than Emax = 0.685 yr−1 and E0.1 = 0.551 yr−1 as biological reference points, which indicates that the stock of Saurida tumbil in Jizan fisheries is currently overexploited.